Mannitol treatment is not effective in therapy of rabies virus infection in mice - Dufkova, Lucie; Sirmarova, Jana; Salat, Jiri; Hönig, Václav; Palus, Martin; Růžek, Daniel; Fooks, Anthony R; Mansfield, Karen L; Tordo, Noël; Jochmans, Dirk; Neyts, Johan; Martina, Byron; et al. (Vaccine, 2019)
Rabies is a deadly viral disease with an extremely high fatality rate in humans. Previously, it was suggested that an enhancement of the blood-brain barrier (BBB) permeability, which allows immune cells and/or antibodies to enter the central nervous system (CNS) tissue, is critical to clear the infection. In this study, we utilised mannitol to increase BBB permeability in mice infected with highly pathogenic silver-haired bat rabies virus (SHBRV). We found that intraperitoneal injection of mannitol causes a slight, transient increase of BBB permeability in the treated mice. SHBRV-infected mice were treated with intraperitoneally administered mannitol daily from day 3 or day 4 post-infection, but no effect of this treatment on the time of disease onset, clinical signs or survival was observed. This data indicates that the increase of BBB permeability by mannitol is not efficient in promoting CNS virus clearance in SHBRV-infected mice.
Keywords: Animals; Female; Mannitol; Rabies virus; ženské pohlaví; Antigens, Viral; Mice; antigeny virové; Blood-Brain Barrier; virus vztekliny; myši; hematoencefalická bariéra; protilátky virové; mannitol; Central Nervous System; Rabies; vzteklina; zvířata; centrální nervový systém; Antibodies, Viral; Mice, Inbred C57BL; myši inbrední C57BL